Changes in the composition of the indoor bioaerosol as a result of the ozonation process carried out under different ventilation air flow rate - Mucha, Walter; Zabłocka-Godlewska, Ewa; Mierzejowska, Aleksandra Mierzejowska; Borkowski, Alex (Instal, 2024)
The microbial composition of indoor bioaerosol is very important for the health and well-being of occupants of these spaces. The efficiency of the ventilation system is crucial in providing proper quality of that. The study aimed to assess the impact of the ozonation carried out under a changeable ventilation air flow rate on airborne microflora. Studies were conducted in a chemical laboratory with four-level force mechanical ventilation. An ozone generator with an efficiency of 1000 g O3/min was used. The impact method was used for the sampling of airborne bacteria and fungi. The number of psychrophilic, mesophilic bacteria and fungi was estimated as CFU/m3. For the growth of bacteria and fungi TSA and Sabouraud medium was used respectively. Temperature, relative humidity (RH), volumetric air flow rate (VFR), and ozone concentration were measured. The average minimum ozone concentration reached after 20 minutes of work of one ozone generator was 0.23 ppm (VFR 0.036 m3/s) and the average maximum concentration was 0.585 ppm (VFR 0.004 m3/s) which resulted in the reduction of number of mesophiles 31.7%, 70.2% and psychrophiles 32.7%, 75.3% respectively. After simultaneous work of two ozone generators the average ozone concentration was 0.96 ppm (VFR 0.122 m3/s) resulted in disinfection efficiency 43.5% and 9.7% respectively. It was difficult to find any tendency of elimination of fungi. The increase of RH of air cause increase the ozonation efficiency towards the airborne fungi, which was not observed in the case of bacteria. The results of disinfection efficiency carried out in the real conditions showed that the number of the airborne bacteria detected after ozonation depended on the biocidal effect of ozone concentration as well as the value of the VFR and time of exposition.
Keywords: bioaerosol; ozonation; disinfection; air quality; indoor air; mechanical ventilation; airborne bacteria; airborne fungi